Resiliensi Pendeta dalam Menghadapi Disrupsi Artificial Intelligence terhadap Pelayanan Pastoral dan Otoritas Spiritual dalam Menghadapi Tantangan Okultisme - Sentosa Sentosa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of Artificial Intelligence (AI) has significantly transformed church ministry and pastoral care through its application in communication, sermon preparation, basic counseling, and digital ministry. Alongside these benefits, AI has also generated new challenges in the form of virtual spiritual phenomena and pseudo-occultism, including spiritual chatbots, digital tarot readings, simulated spirit communication, and religious deepfakes that influence the spiritual perceptions of digital society. These developments raise important questions regarding the limitations of AI in pastoral ministry and its impact on pastoral identity and spiritual authority. This study aims to analyze pastoral resilience in responding to the disruption of Artificial Intelligence toward pastoral ministry and spiritual authority amid the challenges of digital occultism. The theological foundation of this study is based on Mark 16:17, which emphasizes the spiritual authority of believers in ministry empowered by God. This research employs a qualitative method using a literature review approach that draws on practical theology, pastoral studies, and digital technology literature. The findings indicate that AI can support church ministry in technical and communicative functions but cannot replace the pastoral role that requires empathy, discernment, divine wisdom, and spiritual sensitivity. Therefore, pastoral resilience remains essential for maintaining the existence and spiritual authority of pastoral ministry in the era of Artificial Intelligence.